An air-stable Dy(iii) single-ion magnet with high anisotropy barrier and blocking temperature. Issue 8 (3rd May 2016) - Gupta, Sandeep K.; Rajeshkumar, Thayalan; Rajaraman, Gopalan; Murugavel, Ramaswamy
Abstract : A mononuclear Dy(iii ) complex assembled just from five water molecules and two phosphonic diamide ligands combines the advantages of high anisotropy barrier, high blocking temperature and significant coercivity, apart from its remarkable air- and moisture-stability. Abstract : Herein we report air-stable Dy(iii ) and Er(iii ) single-ion magnets (SIMs) with pseudo- D 5h symmetry, synthesized from a sterically encumbered phosphonamide, t BuPO(NH i Pr)2, where the Dy(iii )-SIM exhibits a magnetization blocking ( T B ) up to 12 K, defined from the maxima of the zero-field cooled magnetization curve, with an anisotropy barrier ( U eff ) as high as 735.4 K. The Dy(iii )-SIM exhibits a magnetic hysteresis up to 12 K (30 K) with a large coercivity of ∼0.9 T (∼1.5 T) at a sweep rate of ∼0.0018 T s −1 (0.02 T s −1 ). These high values combined with persistent stability under ambient conditions, render this system as one of the best-characterized SIMs. Ab initio calculations have been used to establish the connection between the higher-order symmetry of the molecule and the quenching of quantum tunnelling of magnetization (QTM) effects. The relaxation of magnetization is observed via the second excited Kramers doublet owing to pseudo-high-order symmetry, which quenches the QTM. This study highlights fine-tuning of symmetry around the lanthanide ion to obtain new-generation SIMs and offers further scope for pushing the limits of U eff and T B using this approach.